P689 Aeromonas infection and Inflammatory Bowel Disease: a single tertiary center analysis. (27th May 2021) - Alves Da Silva, J; Pereira Guedes, T; Falcão, D; Neves, S; Costa, P; Lago, P; Pedroto, I; Salgado, M
Abstract: Background: Aeromonas genus consists of gram-negative rods known to cause a spectrum of diseases in humans. Inflammatory bowel disease (IBD) is an idiopathic complex condition where multiple factors contribute to its development and progression. The association of Aeromonas infection with IBD manifestation have been proposed by other authors and is still largely unknown. We aim to look for the significance of Aeromonas infection and for significant differences between IBD and non-IBD patients. Methods: A retrospective observational data retrieval and analysis was performed of all patients positive for Aeromonas in stool cultures, during a 10-year period, from a Portuguese tertiary and university setting hospital. Results: Fifty patients, 56% of male sex and with a mean age of 42.1 years-old were included. Thirty-eight (76%) were non-IBD and 12 (24%) were IBD patients. IBD patients were more frequently under immunosuppressors. Two patients were asymptomatic and 44% develop mild, 44% moderate and 16.7% severe infection. The main Aeromonas strains isolated were Aeromonas hydrophila/caviae . Co-isolation with other bacteria was found in 4 non-IBD patients and histological findings compatible with Cytomegalovirus were found in 2 IBD patients. Non-IBD patients presented more frequently with fever and IBD patients with bloody diarrhea and abdominal pain. There was higher tendency for severe infection rate in IBD patients with higher antimicrobial therapy use. Steroids were exclusively used in IBD group. No significant differences were observed for isolation of Aeromonas resistant strains. From the IBD, 4 patients had the diagnosis of Ulcerative Colitis and 9 of Crohn's Disease with colonic involvement. Of them 5 patients received the diagnosis after the acute episode of Aeromonas infection . Conclusion: Clinical presentation of Aeromonas infection differ between IBD and non-IBD patients. Non-IBD patients had milder severity of infection with less use of antibiotics. Aeromonas infection seem to play an important role on the contribution of IBD manifestation.